Seroprevalence of viral and bacterial agents in equids from Monte Negro Municipality, State of Rondônia - Aguiar, Daniel Moura; Cavalcante, Guacyara Tenório; Lara, Maria do Carmo Custodio de Souza Hunold; Villalobos, Eliana Monteforte Cassaro; Cunha, Elenice Maria Siquetin; Okuda, Liria Hiromi; Stéfano, Eliana de; Nassar, Alessandra Figueiredo de Castro; Souza, Gisele Oliveira; Vasconcellos, Silvio Arruda; Labruna, Marcelo Bahia; Camargo, Luis Marcelo Aranha; et al. (Brazilian Journal of Veterinary Research and Animal Science, 2008)
Sera from 174 equidaes (15 mules and 161 equines) of Monte Negro municipality, Rondônia State were analyzed against viral and bacterial agents. The serum sample corresponded the total equid population in the municipality considering a confidence interval of 99%, expected prevalence of 50% and absolute desired of 10%. For the viral agents, sera were tested by the Agar Gel Immunodiffusion Test (Equine Infection Anemia - EIA), Inhibition Haemagglutination Test (Equine Influenza 1 and 2 EI1 and 2), and Virusneutralizating Tests (Equine Viral Arteritis EVA, Equine Herpesvirus 1 EHV1, Vesicular Stomatitis VS, Equine Encephalitis Eastern - EEE, Western - WEE and Venezuelan VEE). The diagnosis for brucellosis was made by Agglutination Tests and the Microscopic Agglutination Test was used for leptospirosis. The results showed positivity of 9.6% for EIA, 22.7% for HVE1, 19.9% for IE-1, 42.0% for IE-2, 21.0% for EEE, 11.3% for VEE, 3.4% for brucellosis, and 91.4% for leptospirosis. The most frequent serovars detected were Bratislava (10.5%), Icterohaemorrhagiae (8.7%), Autumnalis (8.7%) for equines and Patoc (26.6%) for mules. No one of the examined samples reacted to EVA, VS, or WEE.